University Outreach: An Immodest Proposal - Margaret S. Andreasen (Journal of Applied Communications, 1985)
In Wisconsin we accord a grand mission to our university system: "The boundaries of the campus are the boundaries of the state ... . " (3, pp. 4-7) The University thus has an educational responsibility for all of the state's citizens. Somehow it must creatively satisfy the information needs of individuals far more diverse than traditional students.